Understanding the Continuance Behavior towards E-Learning: A Systematic Literature Review - Hidayatullah, Elha Dhanny; Santosa, Paulus Insap; Rizal, Muhammad Nur (2022)
Performing users' behavior analysis on elearning is very important for education, especially in formulating and developing a distance education platform with a better learning experience and can provide a more efficient and accurate evaluation of e-learning for continuing education. There are 20 recent studies in continuance behavior towards elearning from January 2018 to April 2022. To provide a more comprehensive overview of continuance behavior towards elearning, a Systematic Literature Review (SLR) was conducted. Three research question conducted to recognize and assess research methods and major theories used in continuance behavior towards e-learning, as well as identify factors that influence sustainable behavior towards elearning. 18 different basic theories (like TAM, TPB, ECM, UTAUT, etc.) or models with 92 kinds of factors were identified and seven factors were dominants to used in research about continuance behavior towards e-learning. The result show that there is one method that is suitable to be used as base model in research about continuance behavior towards e-learning. Most importantly, this study provides a theoretical basis for further research in this context. © 2022 IEEE.